Geochronology of mesozoic large Igeous Provinces in NE Brazil - Oliveira, Alisson Lopes (2022)
The formation of large igneous provinces (LIPs) is directly associated with global geological events that include rupture of (super)continents, opening of oceans and biotic crises. It is not unexpected, therefore, that the study of LIPs remains one of the most important topics on the scientific frontier, whose multidisciplinary profile includes the areas of Petrology, Geochemistry, Geochronology, among others. In this doctoral project, the focus is the geochronological characterization of igneous products exposed in the NE region of Brazil and related to the Central Atlantic Magmatic Province (CAMP) and the Equatorial Atlantic Magmatic Province (EQUAMP). The CAMP is dated to ca. 201 Ma and is correlated with the opening of the Central Atlantic Ocean. In NE Brazil, these rocks occur in the form of dykes, basaltic flows, and sills with a geochemical signature of tholeiitic magmas, identified both in the (Paleozoic) Parnaíba Basin and in the (Precambrian) Borborema Province. The CAMP is known to be represented by mafic lavas at the western edge of the basin, and intrusive bodies (dykes and sills) at the eastern edge. The EQUAMP is distinguished by mafic dyke swarms that total approximately 2,000 km in length, intrusive in the Precambrian basement, and mafic sills restricted to the eastern edge of the Paraníba basin. CAMP and EQUAMP are characteristically constituted by low-Ti (TiO2 <2% wt.%) and high-Ti (TiO2 >2% wt.%) tholeiitic diabases, with CAMP magmas dominated by the low-Ti signature, while in the EQUAMP predominate high-Ti magmas. The characterization of the age of formation of these magmatic provinces required a multi-technical approach, given their continental dimensions and scarcity of previous geochronological data. Techniques included unspiked K/Ar dating (in whole rock) with supporting 40Ar/39Ar dates, and U-Pb dating by chemical abrasion and isotopic dilution (in zircon), aiming to: (1) establish age patterns (Jurassic or Cretaceous) of the various dyke swarms until then not investigated by any geochronological method; (2) to obtain precise ages of the two events CAMP and EQUAMP, in the various investigated targets; (3) discuss the duration of each event considering the modern understanding of LIPs short (<5 Ma) or long (>5 Ma) duration, especially for the EQUAMP; and (4) discuss geodynamic and paleoenvironmental implications. In addition to the effort to obtain scientific data, this project included the implementation of analytical routines, including a new method for recovering zircon from (sub)volcanic mafic rocks. As a main result, this thesis shows that EQUAMP magmatism largely affects NE Brazilian terranes and is unequivocally related to the Weissert (Valanginian) event of paleoenvironmental changes, while also sharing geographic/geological areas previously affected by CAMP magmas. The relationship between CAMP and the Triassic biotic crisis is discussed on a different point of view to that currently proposed in the literature.